2018
DOI: 10.1021/acs.langmuir.8b02534
|View full text |Cite
|
Sign up to set email alerts
|

Poroelasticity of Methane-Loaded Mature and Immature Kerogen from Molecular Simulations

Abstract: While hydrocarbon expulsion from kerogen is certainly the key step in shale oil/gas recovery, the poromechanical couplings governing this desorption process, taking place under a significant pressure gradient, are still poorly understood. Especially, most molecular simulation investigations of hydrocarbon adsorption and transport in kerogen have so far been performed under the rigid matrix approximation, implying that the pore space is independent of pressure, temperature, and fluid loading, or in other words,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 53 publications
2
73
0
Order By: Relevance
“…We also report the same quantities in the LEF case but with diffusion in the nanoporous phase described by a more general free-volume model that accounts for adsorption-induced swelling ( SI Appendix ), which leads to an exponential increase as a function of pressure (46, 47). Due to swelling, the adsorption isotherm evolves linearly with P (until P > 50 MPa) (48), thus lowering the impact of sorption on transport at the mesoscale. As a result, mesopores do not induce a qualitative change on the transport behavior at the mesoscale.…”
Section: Resultsmentioning
confidence: 99%
“…We also report the same quantities in the LEF case but with diffusion in the nanoporous phase described by a more general free-volume model that accounts for adsorption-induced swelling ( SI Appendix ), which leads to an exponential increase as a function of pressure (46, 47). Due to swelling, the adsorption isotherm evolves linearly with P (until P > 50 MPa) (48), thus lowering the impact of sorption on transport at the mesoscale. As a result, mesopores do not induce a qualitative change on the transport behavior at the mesoscale.…”
Section: Resultsmentioning
confidence: 99%
“…26 However, flexible kerogen models have been considered, where they exhibited an increase in gas diffusivity with respect to rigid kerogens due to fluctuations in the pore connectivity. [27][28][29][30] Due to their robust properties, the representative molecular models have become a preferential approach for modeling shale matrices with a broad diversity of physical properties such as TOC, density, porosity, and permeability, as demonstrated by the growing number of molecular simulation studies found in the literature. For example, Collell et al 31 performed MD simulations of hydrocarbons permeating through oil-prone type II kerogen, and found the permeation mechanism is purely diffusive.…”
mentioning
confidence: 99%
“…The PSD can evolve in a complex manner upon adsorption, due to the inhomogeneity of the microscopic deformations, as was shown numerically for a microporous carbon in presence of methane [40]. The PSD being in fact stress-dependent, Siderius et al [41] showed that how the PSD evolves over the adsorption process theoretically contains information related to the flexibility and deformation characteristics of the adsorbent.…”
Section: Specific Complexities For Prediction Of Adsorption-induced Smentioning
confidence: 91%